A novel dental infiltration resin based on isosorbide-derived dimethacrylate with high biocompatibility, hydrolysis resistance, and antibacterial effect - Yang, Su; Sui, Baiyan; Cui, Yinan; Liu, Xin; Sun, Jiao; Wang, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: The available infiltration resin has raised biosafety and treatment stability concerns because of the cytotoxicity of the main component, TEGDMA, and its susceptibility to hydrolysis in the oral environment. This study aimed to develop a TEGDMA-free infiltration resin to overcome these drawbacks. Methods: Using the synthetic bioderived monomer bis(methacrylate) isosorbide (IBM) and the zwitterionic compound 2-methacryloyloxyethyl phosphorylcholine (MPC), a novel infiltrant IBMA was developed and preferentially selected. We investigated the performance of the IBMA resin regarding cytotoxicity, antibiofilm adhesion, and hydrolysis resistance and further verified its ability to restore the demineralized enamel and stability of the infiltrated area under artificial aging conditions. Results: Compared with the commercial TEGDMA-based infiltration resin ICON, IBMA not only demonstrated similar enamel morphologic and esthetic restorative effects in chalky lesions but also exhibited favorable cell viability, durable Streptococcus mutans UA159 biofilm-repellent performance, and higher enamel microhardness (204.0 ± 5.12 HV) of the infiltrated enamel. Specifically, because of the high crosslink density [(47.77 ± 5.76) ×103 mol/mm3] and low water sorption [12.79 ± 2.56 µg/mm3] of the polymer network, the IBMA resin was more resistant to hydrolysis than ICON, which prevents the disruption of the infiltrant’s micropore-blocking effect after aging. Enamel lesions treated with IBMA demonstrated good color stability after the tea-staining challenge, which was significantly better than that in the ICON group. Conclusion: Based on these findings, the IBMA resin exhibits favorable cell viability, hydrolysis resistance, and biofilm-repellent properties, which alleviates the defects of traditional TEGDMA systems. Therefore, it is a better alternative for microinvasive treatment involving early caries and enamel whitish discoloration.